PROMOTION OF BANKING SERVICES USING THE SOCIAL NETWORK INSTAGRAM - Blahun, I.I.; Nianko, L.Y.; Biloshkurska , N. V. (The actual problems of regional economy development, 2023)
The article examines the promotion of banking services using the social network Instagram, analyzes which social networks are used by users in Ukraine. The advantages of using the Instagram social network to improve the promotion of banking services are identified. The purpose of the article is to study the social network Instagram as a modern tool for promoting banking services, to identify the main factors of ER influence, to analyze the advantages and disadvantages of this method of promotion and to assess the effectiveness of its use by banking institutions. The advantage of this network is the large coverage of both existing bank customers and potential customers. It is found that scientists are increasingly coming to promote products through social networks of various types. It has been researched that the calculation of the Engagement Rate indicator makes it possible to facilitate and improve the work of the marketing department in the following areas: SMM, personalization and communication with customers, selection of the target audience, audience loyalty to the brand, its needs and reach, content creation, etc. The number of subscribers to banks' social media pages is noteworthy, ranging from thousands to hundreds of thousands. The fluctuation of the audience and its engagement is inherent in both state-owned and commercial banks. In addition, it is worth noting the presence of the regulator's page on the social network, where the number of subscribers is not very significant. The number of subscribers correlates with the activity of the audience on the page. Banks with a high level of user activity and banks that have maneuvers for development were identified. In general, it is worth noting that the use of social networks is becoming an indispensable tool for both marketers and brands. These social networks are in the process of development and will be the subject of constant research by both scientists and businesses that promote their products or services in the digital environment. The role and place of social networks in the structure of marketing costs will be constantly growing. Companies will resort to professional management of corporate pages on social networks. After all, the indicator of audience engagement or activity has a constant impact on other factors of the marketing environment. This, in turn, forms the content's fidelity, which directly affects the brand's popularity by determining its place in comparison with other brands in a particular social network.